Development of Video Media Based on Local Wisdom in Introducing Cultural Literacy to Early Childhood at Idhata Pontianak Kindergarten - Laura; Diana; Iin Maulina (Tunas Siliwangi, 2024)
The research aims to develop video media based on local wisdom to introduce cultural literacy to early childhood at Idhata Kindergarten. The problem encountered is that educators only use image media during learning activities. The method used is research and development (R&D) ADDIE model consisting of five stages, namely analysis, design, development, implementation and evaluation. Data collection includes questionnaires, interviews and documentation. The analysis technique uses quantitative data analysis and qualitative data. The results obtained in this study show the average value in conducting the trial, namely that the small group obtained a score of 3.48 and the large group obtained a score of 3.68 with good criteria. Based on the explanation, it can be concluded that the development of video media based on local wisdom can be used to introduce cultural literacy to early childhood children aged 5-6 years.